Forced Degradation Study of Flavonoid in Portulaca grandiflora extract using Spectrophotometric UV-Vis - Erlien Dwi Cahyani; Titah Amalia Suharyanto; Maria Fatmadewi Imawati (Universitas STRADA Indonesia, 2026)
Exploration of the effectiveness from magenta purslane herb extract in traditional medicine is still ongoing. Flavonoid is the major compound that allegedly have pharmacology effect in magenta purslane herb extract. To ensure the stability of the flavonoid content in the magenta purslane herb extract, a stability test was carried out using forced degradation. The aim of this study was to determine the effect of forced degradation by acid hydrolysis, alkaline hydrolysis, oxidation and heat substanes on the quercetin content of magenta purslane herb extract using a UV-Vis Spectrophotometer at a wavelength of 424 nm. The results showed in the form of a linear regression equation y=0.0127x + 0.0437 with a value of r2 = 0.9912 with a quercetin content of 10.59 %w/w. It was concluded that statistically there was a significant difference with the decrease content in the acid, base and oxidation forced degradation treatments after 2 consecutive hours of 1,65 %w/w; 3,86 %w/w; 2,38 %w/w whereas no significant reduction was observed under thermal degradation.